2010
DOI: 10.1016/j.irfa.2010.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Pyramidal structure, firm capital structure exploitation and ultimate owners' dominance

Abstract: a b s t r a c tIn this paper we investigate how pyramid structure, separating cash flow rights and control rights, allows ultimate owners to control the company's resources for the creation of private benefits and to avoid punishment for such conduct. Empirical tests are conducted using three-stage least squares regression. The estimated results provide support for the hypotheses proposed that the separation of cash flow rights and control rights have led to the use of excess leverage among pyramidal companies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 61 publications
0
14
0
1
Order By: Relevance
“…Due to the existence of interest rate tax shields, financing with debt instead of equity increases a firm's market value (Miller, 1977;Miller & Modigliani, 1963;Myers, 2001). Nevertheless, an increase of the firm's debt levels increases financial distress costs (Bany-Ariffin et al, 2010;Miller & Modigliani, 1963;Philosophov & Philosophov, 1999, 2005Titman, 1984) and agency conflicts between the firm's bondholders and stockholders (Jensen and Meckling, 1976;Frankfurter and Philippatos, 1992). DeAngelo and Masulis (1980) and Harris and Raviv (1991) conclude that firms with safe, tangible assets and large profits to shield should exhibit higher debt ratios than unprofitable companies with risky, intangible assets, high advertising expenditures and unique products that should rely mostly on equity finance.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the existence of interest rate tax shields, financing with debt instead of equity increases a firm's market value (Miller, 1977;Miller & Modigliani, 1963;Myers, 2001). Nevertheless, an increase of the firm's debt levels increases financial distress costs (Bany-Ariffin et al, 2010;Miller & Modigliani, 1963;Philosophov & Philosophov, 1999, 2005Titman, 1984) and agency conflicts between the firm's bondholders and stockholders (Jensen and Meckling, 1976;Frankfurter and Philippatos, 1992). DeAngelo and Masulis (1980) and Harris and Raviv (1991) conclude that firms with safe, tangible assets and large profits to shield should exhibit higher debt ratios than unprofitable companies with risky, intangible assets, high advertising expenditures and unique products that should rely mostly on equity finance.…”
Section: Introductionmentioning
confidence: 99%
“…It was also identified that if projects fail the impact on the UO is limited as the problem would be confined to the lower level firm and its debt-holders. This argument by Bany-Ariffin et al (2010), and others such as Vera and Ugedo (2007), may go some way to explain excessive gearing in some circumstances; however, they have little bearing on tax shield effects. This is because tax shield benefits are enjoyed at the individual firm level no matter what the group structure is.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 85%
“…This study addresses Malaysian listed firms in term of ownership-control structure mechanisms are pyramidal-ownership structure and golden share [6].The following section addresses pyramidal ownership structure and golden shares.…”
Section: Mechanisms For Separating Cash Flow and Controlmentioning
confidence: 99%